Schulden und Staatlichkeit: Überlegungen zur Politischen Ökonomie des Schuldenstaats - Rainer Klump (IBF - Institut für Bank- und Finanzgeschichte e.V., 2022)
– The paper starts with a view on public debt as a current and historical phenomenon. Then follows a short review of traditional explanations for the debt-state link. Three different approaches are distinguished, the first one building on institutional economics, the second one on applications of sociology on historical development patterns, and the third one developing several theories of stages that all end with the modern tax state as put forward by Joseph Schumpeter. The concept of the tax state will then be contrasted with the concept of a debt state whose political, economic, and institutional structures can be studied in an analytical framework developed by David Stasavage. When applying these considerations to the Holy Roman Empire one must highlight the essential role of the Imperial Aulic Council and its debt commissions. They created a surprisingly stable institutional framework that permitted a high degree of capital mobility among the territories of the Empire and at the same time helped to stabilize the authority of the emperor as the protector of the many smaller and weaker members of the Empire. Finally, it is shown by some selected examples how the problems of public debt all over Europe before 1800 contributed to the development of economics as a science and how the new scientific knowledge also influenced political decision-making within the debt state and during itstransition to the modern taxstate.
Keywords: P00; H63; H71; N40; 330; Hamilton Moment; Public Debt; Tax State; Holy Roman Empire; DebtCommissions